2007
DOI: 10.1111/j.1556-4029.2007.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint Reagents with Dual Action: Color and Fluorescence

Abstract: We define "dual fingerprint reagents" as chemical formulations that produce with latent fingerprints in one stage impressions that are both colored and fluorescent. Solutions containing ninhydrin and group IIb metal salts appear to be true dual reagents. Application of these formulations to latent fingerprints on paper is as efficient as the two-step process beginning with ninhydrin and followed by treatment with metal salt. In the color mode, fingerprint detectability with the two ninhydrin-metal salt reagent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Lowering the temperature to −200°C was not necessary–it only marginally increased the fluorescence. Like in the previous study with unsubstituted ninhydrin (1), it seems that the metal ions, which are pre‐mixed with the ninhydrin analogues, do not interfere with the reaction with amino acids and they react only with the initially formed Ruhemann’s purple. The metal ions could potentially prevent the formation of Ruhemann’s purple by reacting with the many intermediates that are formed in the ninhydrin reaction with amino acids, but this is not the case.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Lowering the temperature to −200°C was not necessary–it only marginally increased the fluorescence. Like in the previous study with unsubstituted ninhydrin (1), it seems that the metal ions, which are pre‐mixed with the ninhydrin analogues, do not interfere with the reaction with amino acids and they react only with the initially formed Ruhemann’s purple. The metal ions could potentially prevent the formation of Ruhemann’s purple by reacting with the many intermediates that are formed in the ninhydrin reaction with amino acids, but this is not the case.…”
Section: Resultssupporting
confidence: 65%
“…The results were compared with those obtained with DFO under the same conditions, in the color and fluorescence modes. Results were also compared with those obtained with the ninhydrin–zinc chloride dual reagent, on which we reported earlier (1). For a more accurate, semi‐quantitative comparison, similar experiments were also carried out on amino acid stains of known concentrations.…”
mentioning
confidence: 99%
“…It was found that ninhydrindeveloped marks, when posttreated with a metal salt and cooled with liquid nitrogen, exhibited photoluminescence, which could be used to significantly enhance detection sensitivity and contrast [75]. Since these early studies, the main focus of amino acid-reagent research has been on developing reagents that exhibit good color and superior photoluminescence without the need for additional treatments (such as metal salt treatment or cooling) [112]. Photoluminescence is observed by illuminating the developed fingermark with a filtered light source (or laser) and viewing through appropriate filters (Fig.…”
Section: Detection Of Latent Fingermarksmentioning
confidence: 99%
“…During the last few years, a series of indanedione compounds were synthesized [7] and reported in the literature for their fluorescent properties [8,9]. Although substituted indane-1,3-dione derivatives have been used in the fields of medicine [10] and biology [11], literature data on their chemical and physical interactions with proteins is scarce [12,13], and no chemical and physical studies of their interaction with immunoglobulins, and their applicability as fluorescent labels were found.…”
Section: Introductionmentioning
confidence: 99%